The Chaperonin TRiC/CCT Inhibitor HSF1A Protects Cells from Intoxication with Pertussis Toxin - Jia, Jinfang; Zoeschg, Manuel; Barth, Holger; Pulliainen, Arto T.; Ernst, Katharina (MPDI, 2025)
Pertussis toxin (PT) is a bacterial AB5-toxin produced by Bordetella pertussis and a major molecular determinant of pertussis, also known as whooping cough, a highly contagious respiratory disease. In this study, we investigate the protective effects of the chaperonin TRiC/CCT inhibitor, HSF1A, against PT-induced cell intoxication. TRiC/CCT is a chaperonin complex that facilitates the correct folding of proteins, preventing misfolding and aggregation, and maintaining cellular protein homeostasis. Previous research has demonstrated the significance of TRiC/CCT in the functionality of the Clostridioides difficile TcdB AB-toxin. Our findings reveal that HSF1A effectively reduces the levels of ADP-ribosylated Gαi, the specific substrate of PT, in PT-treated cells, without interfering with enzyme activity in vitro or the cellular binding of PT. Additionally, our study uncovers a novel interaction between PTS1 and the chaperonin complex subunit CCT5, which correlates with reduced PTS1 signaling in cells upon HSF1A treatment. Importantly, HSF1A mitigates the adverse effects of PT on cAMP signaling in cellular systems. These results provide valuable insights into the mechanisms of PT uptake and suggest a promising starting point for the development of innovative therapeutic strategies to counteract pertussis toxin-mediated pathogenicity.